Vulnerability analysis of GPS receiver software - Gonzalez, G. Mori; Petrunin, Ivan; Zbikowski, Rafal; Voutsis, K.; Verdeguer Moreno, Ricardo (IEEE, 2019)
Satellite navigation systems such as the Global Positioning System (GPS)makes it possible for users to find their relative or absolute position. Thanks to its mobility and reliability, the GPS is used in many civil and military applications. However, the GPS does not provide an advanced level of security. Therefore, it could be potentially a target of attacks. With the development of new GPS attacks, the security knowledge has to grow at the same rate, so existing attacks can be detected by updated versions of receiver software or hardware. In this paper, a comparative analysis of GPS receiver resilience to software attacks is performed with the help of GNSS simulator from Spirent. The main objective of this work is to perform a sensitivity analysis of variables involved in calculation of position of the GPS receivers from different price bands that might be targeted by existing or future GPS attack. Variables making the biggest impact on calculated position are determined using the model. Experimentation validation of their influence is performed using selected receivers and corrupted signals generated by GNSS simulator. The testing is based on tuning the selected variables in order to simulate the theoretical error obtained from the sensitivity analysis. The results obtained from testing are discussed in order to analyse the behaviour of the considered GNSS receivers (including the premium class ones)and establish whether they provide a protection from existing or potential GPS attacks.
Keywords: GPS; Security; GNSS; RF Attacks; Spoofing; GSS 7000; Spirent